Predictive value of the UICC and AJCC 8th edition tumor-nodes-metastasis (TNM) classification for patients treated with radical prostatectomy. (October 2018) - Herden, Jan; Heidenreich, Axel; Wittekind, Christian; Weissbach, Lothar
Highlights: cT1/cT2 and Stage I/II grouping is feasible to predict a different pT-category after RP. cT1/cT2 and Stage I/II grouping is feasible to predict a favorable WHO-grade after RP. Prognostic Stage Groups incorporate PSA and WHO grade into T-Category. Only Prognostic Stage Groups predicted a different Biochemical Free Survival. Prognostic Stage Groups are useful to help clinicians in advising their patients. Abstract: Background: According to the 8 th -edition of the tumor-nodes-metastasis-classification localized prostate cancer (PCa) can be divided into two categories (cT1, cT2), two stages (SI, SII), and, by incorporating prostate-specific-antigen (PSA) and WHO-grade (Gleason-Score), into prognostic stage groups (PSG I, IIA, IIB, IIC, III). We examined the predictive value of these systems for an organ-confined disease (pT≤2), favorable WHO-grade ≤2 (Gleason-score ≤7a), and biochemical-free-survival (BFS) after radical prostatectomy (RP). Methods: Data were collected in a prospective, non-interventional, multicenter health-service-research study for the treatment of localized PCa (HAROW) with 687 patients receiving RP. Mean Follow-up was 31.7 months. Results: Organ-confined disease was present in 76.5% and 63.6% of cT1 and cT2 patients, 75.7% and 59.6% of SI and SII, and 84.6%, 81.6%, 72.8% and 42.5% of PSG I, IIA, IIB and ≥ IIC (p = 0.001). Favorable WHO-grade (Gleason-Score) was present in 75.4% and 60.7% of cT1 and cT2 patients, 74.3% and 56.5% of SI and SII patients, and 86.1%, 85.6%, 73.3% and 29.5% of PSG I, IIA, IIB and ≥ IIC (p = 0.001). Probability of BFS was 92.0% and 91.5% for cT1 and cT2 (p = 0.990), 91.1% and 94.2% for SI and S II (p = 0.286) and 96.6%, 95.1%, 91.4% and 78.8% for PSG I, IIA, IIB and ≥ IIC (p = 0.001). Conclusions: CT 1/cT2 and S I/II subgrouping is feasible to predict a different pT-category and a favorable WHO-grade (Gleason-Score) after RP, but failed to predict a different BFS. With the additional information of WHO-grade (Gleason-Score) and PSA, the PSG represents an approach for the prediction of all examined endpoints which is a useful tool to help clinicians to advise their patients.